2005
DOI: 10.1111/j.1747-0285.2005.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Amyloid Fibril Formation by Polyphenols: Structural Similarity and Aromatic Interactions as a Common Inhibition Mechanism

Abstract: The formation of well-ordered fibrillar protein deposits is common to a large group of amyloidassociated disorders. This group consists of several major human diseases such as Alzheimer's disease, Parkinson's disease, prion diseases, and type II diabetes. Currently, there is no approved therapeutic agent directed towards the formation of fibrillar assemblies, which have been recently shown to have a key role in the cytotoxic nature of amyloidogenic proteins. One important approach in the development of therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
929
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 924 publications
(967 citation statements)
references
References 72 publications
34
929
1
3
Order By: Relevance
“…These results are also important in the context of the treatment of amyloidoses in general, insofar as they support the increasingly accepted notion that all diseases that involve the pathological aggregation of a particular protein might share common mechanisms and common therapeutic interventions. 75,76 Indeed, other examples of compounds able to inhibit the aggregation of several amyloidogenic proteins have been reported. 40,75,77 Protection Against the Synaptic Failure Induced by Aβ Oligomers in Hippocampal Slices of C57bl6 Mice.…”
Section: Inhibition Of Aβ42 and Tau Aggregation In Intactmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are also important in the context of the treatment of amyloidoses in general, insofar as they support the increasingly accepted notion that all diseases that involve the pathological aggregation of a particular protein might share common mechanisms and common therapeutic interventions. 75,76 Indeed, other examples of compounds able to inhibit the aggregation of several amyloidogenic proteins have been reported. 40,75,77 Protection Against the Synaptic Failure Induced by Aβ Oligomers in Hippocampal Slices of C57bl6 Mice.…”
Section: Inhibition Of Aβ42 and Tau Aggregation In Intactmentioning
confidence: 99%
“…75,76 Indeed, other examples of compounds able to inhibit the aggregation of several amyloidogenic proteins have been reported. 40,75,77 Protection Against the Synaptic Failure Induced by Aβ Oligomers in Hippocampal Slices of C57bl6 Mice. In the light of the outstanding multi-target pharmacological profile found in vitro and in E. coli cells for the enantiopure rhein-huprine hybrids (+)-and (-)-7e, involving the modulation of crucial targets of the pathological network of AD, these compounds were selected as leads for further pharmacological characterization.…”
Section: Inhibition Of Aβ42 and Tau Aggregation In Intactmentioning
confidence: 99%
“…7,8 Among the most promising small-molecule inhibitors, the naturally occurring polyphenols show the most effective antiamyloidogenic activity. 9 A group of polyphenols found in green tea (GTPs) including (−)-epigallocatechin (EGC), (−)-epicatechin gallate (ECG), and (−)-epigallocatechin gallate (EGCG) have been reported as effective inhibitors of alkali-saltinduced fibrillogenesis of hen egg white lysozyme (HEWL) with ECG as the most potent polyphenol. 10 A previous report demonstrated that curcumin can also inhibit the aggregation and formation of amyloid fibrillation of HEWL at pH 2.0 in a dosedependent manner.…”
Section: ■ Introductionmentioning
confidence: 99%
“…26,27 Previous polyphenol studies have shown that a minimum of two aryl rings are required for Aβ(1-42) binding, with one ring being a phenolic group which contains at least one hydroxyl substitution and the length of the linker is critical for activity. 27 We therefore synthesized a series of compounds with increasing number and positioning of hydroxyl groups around the phenyl-scyllo-inositol backbone with an oxime linkage, compounds 6−11.…”
Section: ■ Results and Discussionmentioning
confidence: 99%